Heliostat field optimization and comparisons between biomimetic spiral and radial-staggered layouts for different heliostat shapes. (15th May 2022) - Belaid, Abdelfetah; Filali, Abdelkader; Hassani, Samir; Arrif, Toufik; Guermoui, Mawloud; Gama, Amor; Bouakba, Mustapha
Highlights: Comparison of optimized spiral and staggered layouts for different heliostat shapes. The GOA algorithm is used for the first time to optimize the heliostat layout. A circular heliostat shape reduces the land area by 25.9% & 28.4% for both layouts. A circular heliostat shape improves the efficiency to 71% & 71.1% for both layouts. Abstract: During the design and characterization of Solar Power Tower (SPT) systems, the selection and optimization of the heliostat field distribution are critical. Additionally, selecting the appropriate heliostat shape is an important factor to consider because of the optical losses linked to the heliostat shape. In the current study, the optimization and comparison between biomimetic spiral and Campo radial-staggered layout are carried out by considering various heliostat shapes. The optimization is carried out for the PS10 plant installed in Spain. The Grasshopper Optimization Algorithm (GOA) approach is used, and the heliostat field efficiency is assessed. The optimized heliostat field showed that the Campo radial-staggered layout provides better efficiency and the lowest land area when compared to the biomimetic spiral layout. In addition, using a circular heliostat shape for the original PS10 field, the land area could be reduced by 25.86% (about 113, 538 m 2 ) and 28.39% (about 124, 633 m 2 ) for the biomimetic spiral and staggered fields, respectively. On the other hand, for the circular heliostat, the yearly efficiency is improved to ∼ 71 and ∼ 71.1% for biomimetic spiral and staggered fields, respectively, compared to the conventional rectangular heliostat with an efficiency equal to ∼ 69.3%. Indeed, the registered gains in land area and yearly efficiency will reduce the Levelized cost of energy.